Humanist Da’wah Husain Ja'far Al Hadar on Instagram Media: Millennial Generation Perspective - Moch Nurcholis Majid (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2024)
This research aims to find out how millennials perceive the context of humanist da'wah on Instagram media carried out by Husain Ja'far al-Hadar on Instagram media. With a qualitative approach and case study method in a humanist preaching style on the Instagram account @husein_hadar, with data collection techniques using observation, in-depth interviews, and documentation. Meanwhile, data analysis uses reception analysis with the Stuart Hall decoding model and the Fiqh rules of Jum'ah Amin Abdul Aziz's preaching. The results of the research above show that the millennial generation's perception of understanding the concept of humanist da'wah by Husain Jak'far al Hadad on Instagram media is an understanding of giving examples before preaching, binding hearts before explaining, making things easier, not difficult, encouraging before giving threats, students are teachers, not students. Books and there needs to be content that answers society's problems and provides content that explains the humanist message conveyed.